2016
DOI: 10.1186/s12877-016-0381-4
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the association between grip strength and mortality in older adults: results from the KORA-age study

Abstract: BackgroundReduced muscular strength in the old age is strongly related to activity impairment and mortality. However, studies evaluating the gender-specific association between muscularity and mortality among older adults are lacking. Thus, the objective of the present study was to examine gender differences in the association between muscular strength and mortality in a prospective population-based cohort study.MethodsData used in this study derived from the Cooperative Health Research in the Region of Augsbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 41 publications
4
59
3
5
Order By: Relevance
“…***P < 0.001. 21 In our study, RT was significantly associated with heart disease and stroke mortalities in those aged 35-74 years at baseline, with greater HR in the younger birth cohort, and no clear gender difference was shown in the association between GS and CVD mortality. The multivariate model was adjusted for systolic blood pressure, diabetes mellitus, smoking habit, alcohol consumption, radiation dose, total cholesterol and reaction time/grip strength.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…***P < 0.001. 21 In our study, RT was significantly associated with heart disease and stroke mortalities in those aged 35-74 years at baseline, with greater HR in the younger birth cohort, and no clear gender difference was shown in the association between GS and CVD mortality. The multivariate model was adjusted for systolic blood pressure, diabetes mellitus, smoking habit, alcohol consumption, radiation dose, total cholesterol and reaction time/grip strength.…”
Section: Discussioncontrasting
confidence: 47%
“…20 Although studies investigating an association of RT or GS with CVD mortality across different age and gender groups are limited, the Health and Lifestyle Survey showed the effect of different ages on associations between RT and all CVD and stroke mortalities, 5 and the Cooperative Health Research in the Region of Augsburg-Age study showed the effect of different genders on association between GS and CVD mortality. 21 In our study, RT was significantly associated with heart disease and stroke mortalities in those aged 35-74 years at baseline, with greater HR in the younger birth cohort, and no clear gender difference was shown in the association between GS and CVD mortality.…”
Section: Discussioncontrasting
confidence: 47%
“…Sarcopenia is an age‐associated process characterized by a progressive loss of skeletal muscle mass and strength . This condition is a major health concern in older adults because it has been associated with metabolic impairments, cardiovascular disease risk factors, and physical and functional disability and increases the likelihood/risk of early mortality . All these metabolic and physical alterations cause important healthcare costs and significantly affect quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of hand grip strength, which is recognized as a method of predicting body muscularskeletal functioning 12 , it has been demonstrated that low grip strength may result in a greater probability of functional limitations and consequently death 13,14 . In addition, elderly persons with a history of frequent falls have lower levels of hand grip strength and, consequently, lower limb strength levels, than elderly individuals without a history of falls 13 .…”
Section: Introductionmentioning
confidence: 99%